Innovations and Challenges in Primary School English Education in the Industrial Era 4.0 - M. Bambang Purwanto; Fitri Nurdianingsih; Vivin Afini; Nozylianty (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
The existence, dynamics, and applicability of English language instruction at the basic school level to the disruptive technology era are all covered in detail in this study. This paper aims to characterize research problems using descriptive-analytical approaches and research methodologies of the literature study type, utilizing literature data from pertinent books, journals, papers, and scientific publications. This study outlines a number of prerequisites for English language instruction in the modern day, including infrastructure and technology, curriculum and instructional strategies, certified teachers, instructional materials and resources, and parental support. The results also show that there are opportunities that can be targeted, such as more extensive access to language learning materials, dynamic and interesting learning opportunities, global connectivity and language exchange, digital applications for language practice, and the provision of a useful system for evaluation and feedback. In the meanwhile, issues include unequal access to technology, unequal user technical proficiency, linguistic difficulties, students' short attention spans and lack of focus, and threats to digital security.